Shoot smart!. - Whong, Jason
Great weather and summer vacations equal photos-lots of photos-and videos too. But nothing's worse than flubbing a shot you really care about, so we assembled 20 expert tips that run the gamut from shooting with any camera to editing, layout, and printing once you're back at your Mac.
Keywords: Cameras; Camcoders